Analisis Penyelesaian Sengketa Perlindungan Konsumen Diluar Pengadilan Menurut Undang-undang Nomor 8 Tahun 1999 - Taffana Agyarossa; Rani Apriani (Peneliti.net, 2023)
The existence of a trade carried out by business actors which often causes consumers to be harmed which leads to a dispute between consumers and business actors. By going through the consumer dispute resolution process outside the court, the settlement process will be easier. With the enactment of the Republic of Indonesia Law Number 8 of 1999 concerning Consumer Protection, it is hoped that the Indonesian people can understand and be aware of the rights and obligations of business actors in order to be responsible. The type of research used in writing this journal is by using normative legal research methods. There are 3 ways for the Consumer Dispute Settlement process which is carried out outside the court, namely: Conciliation, Mediation and Arbitration.